2019
DOI: 10.1097/dss.0000000000001890
|View full text |Cite
|
Sign up to set email alerts
|

No Additional Benefit of Combining Fractional Carbon Dioxide Laser With Narrow-Band Ultraviolet B Phototherapy for Vitiligo: A Randomized Prospective Study With Half-Body Side Comparison

Abstract: BACKGROUND Narrow-band ultraviolet B (nb-UVB) phototherapy constitutes the gold standard treatment for vitiligo. Whether carbon dioxide (CO2) laser might increase the efficacy of nb-UVB is still a topic of debate. OBJECTIVE To test the hypothesis that the addition of fractional CO2 laser to nb-UVB may enhance repigmentation. PATIENTS AND METHODS Fractional CO2 laser was applied with an interval of 2 weeks fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In meta-analyses, CO 2 laser with NB-UVB was associated with a significantly higher odds of treatment success (OR 2.60, 95% CI 1.05–6.45, p = .04) and lower odds of treatment failure (OR 0.43, 95% CI 0.25–0.72, p = .002) (see Supplemental Digital Content , Figure S2, http://links.lww.com/DSS/B91). 21–26 Feily and colleagues 27 also found evidence of improved repigmentation after autologous transplantation and NB-UVB in patches pretreated with fractional CO 2 laser therapy. Other studies tested the effects of CO 2 ablation in combination with PRP, Er:YAG laser and tacrolimus, dermabrasion combined with Er:YAG laser and 5-FU, 1 versus 2 treatments of CO 2 laser, cryoblebbing combined with cell suspensions and NB-UVB, and CO 2 and NB-UVB with or without betamethasone with varying results.…”
Section: Resultsmentioning
confidence: 97%
“…In meta-analyses, CO 2 laser with NB-UVB was associated with a significantly higher odds of treatment success (OR 2.60, 95% CI 1.05–6.45, p = .04) and lower odds of treatment failure (OR 0.43, 95% CI 0.25–0.72, p = .002) (see Supplemental Digital Content , Figure S2, http://links.lww.com/DSS/B91). 21–26 Feily and colleagues 27 also found evidence of improved repigmentation after autologous transplantation and NB-UVB in patches pretreated with fractional CO 2 laser therapy. Other studies tested the effects of CO 2 ablation in combination with PRP, Er:YAG laser and tacrolimus, dermabrasion combined with Er:YAG laser and 5-FU, 1 versus 2 treatments of CO 2 laser, cryoblebbing combined with cell suspensions and NB-UVB, and CO 2 and NB-UVB with or without betamethasone with varying results.…”
Section: Resultsmentioning
confidence: 97%
“…After browsing the full texts of the included articles, 136 studies were excluded for the following reasons: improper intervention or comparator ( n = 88), not RCT ( n = 43), no relevant outcomes ( n = 10), full‐text unavailable ( n = 5). Only 28 articles 19,25–51 were eligible for inclusion and progressed to the stage of data extraction. Finally, only 22 studies were included in the data analysis since the others had insufficient data.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical trials by Shin et al, 36 Doghaim et al, 37 Ghasemloo et al, 38 and Bakr et al 39 have shown that fractional CO 2 laser combined with narrow‐band ultraviolet B (NB‐UVB) has substantial efficacy when treating non‐segmental vitiligo patients, especially for induced marginal repigmentation 38 . In contrast, clinical trials by El‐Zawahry et al and Esme et al 40,41 found that the combination of fractional CO 2 laser and NB‐UVB in the treatment of non‐segmental vitiligo did not show any significant advantage over NB‐UVB alone. Therefore, Kim et al’s 35 meta‐analysis attempted to determine whether it is more effective to combine the two treatments using statistical methods; the results showed that fractional CO 2 laser combined with NB‐UVB might be more effective for treating non‐segmental vitiligo than NB‐UVB monotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical trials by Shin et al,36 Doghaim et al,37 Ghasemloo et al,38 and Bakr et al39 have shown that fractional CO 2 laser combined with narrow-band ultraviolet B (NB-UVB) has substantial efficacy when treating nonsegmental vitiligo patients, especially for induced marginal repigmentation 38. In contrast, clinical trials by El-Zawahry et al and Esme et al40,41 found that the combination of fractional CO 2 laser and NB-UVB in the treatment of non-segmental vitiligo did not show any significant advantage over NB-UVB alone. Therefore, Kim et al's35…”
mentioning
confidence: 99%